1978
DOI: 10.1137/0715034
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for Solvents of Matrix Polynomials

Abstract: Abstract. In an earlier paper we developed the algebraic theory of matrix polynomials. Here we introduce two algorithms for computing "dominant" solvents. Global convergence of the algorithms under certain conditions is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 5 publications
(1 reference statement)
2
28
0
Order By: Relevance
“…The relation between the Riccati and the quadratic matrix equation is highlighted in [7], whereas a study on the existence of solvents can be found in [13]. Several works address the problem of computing a numerical approximation for the solution of the quadratic matrix equation: an approach to compute, when possible, the dominant solvent is proposed in [12]. Newton's method and some variations are also used to approximate solvents numerically: see for example [11], [22], [21], [27].…”
Section: P (S) := J=0mentioning
confidence: 99%
“…The relation between the Riccati and the quadratic matrix equation is highlighted in [7], whereas a study on the existence of solvents can be found in [13]. Several works address the problem of computing a numerical approximation for the solution of the quadratic matrix equation: an approach to compute, when possible, the dominant solvent is proposed in [12]. Newton's method and some variations are also used to approximate solvents numerically: see for example [11], [22], [21], [27].…”
Section: P (S) := J=0mentioning
confidence: 99%
“…which is dealt by Dennis, Traub and Weber [4]. It has an infinite number of solvents which have a form:…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…The problem of reducing an algebraic Riccati equation to (1.2) has been analyzed in [4]. Numerical methods for solving (1.2) has been considered including two linearly convergent algorithms for computing a dominant solvent [8,10]. Davis [6,7] used Newton's method for solving (1.2).…”
Section: B Hashemi and M Dehghanmentioning
confidence: 99%